Identification key to species of Thrips genus from China (Thysanoptera, Thripidae), with seven new records - Zhang, Hongrui; Xie, Yonghui; Li, Zhengyue (Zootaxa, 2011)
An illustrated key is provided to distinguish the 33 species of genus Thrips recorded from China, including seven species not previously recorded from this country.